Infiltration characteristics of materials enclosed with geobags - Zhou, Hang (2016)
A common problem of slope failures in tropical areas covered by residual soils such as Singapore is caused by rainfall. Geobag is a type of reinforced wall used to protect or stabilize riverbanks, dikes or slopes. It can create the capillary barrier by placing a fine-grained soil layer underlain by a coarse-grained soil layer. It will provide tension force and able to channel rainfall water into the drains hence reducing runoff. The aim of the project is to study the effect of geobag on the infiltration characteristics through the soil column comprising sand overlying gravel (originated from recycled asphalt). Characteristics of the sand, recycled asphat as well as the geobag were tested in laboratory following relevant testing standards. One-dimensional (1-D) soil column study was performed to investigate the effect of the geobag on the characteristic of water infiltration. The soil column tests were performed on two configurations. The first one consists of sand overlying recycled asphalt, and the second one was sand overlying recycled asphalt with one piece of geobag inserted at the interface between the two materials. Each configuration was subjected to two different rainfall patterns. A seepage numerical modeling was conducted to model the 1-D column test. The results from the column study are used to compare with the numerical modeling results.